Development and experiment research of 25 Gbit/s passive optical network - Dan GENG; Yong GUO; Yongjia YIN; Zhuang MA; Weiliang ZHANG (Dianxin kexue)
With the new service development of high-definition video and virtual reality and the requirement of transporting the fifth generation mobile fronthaul/backhaul signals,passive optical network (PON)is required to transmit signals above 10 Gbit/s.When the line rate is above 10 Gbit/s,chromatic dispersion and power budget are the main constraint factor of system performance.Development and difficulty of 25 Gbit/s PON were introduced.25 Gbit/s PON was studied in experiment using 25 Gbit/s EML laser with zero dispersion wavelength,25 Gbit/s APD and 10 Gbit/s APD.Experiment results show that 32 dBm optical power budget（N2 level in 10 Gbit/s symmetric EPON）was achieved when EML transmit optical power is+5 dBm and 25 Gbit/s APD is used without optical amplifier.